Freeze‐dried platelets are a promising alternative in bleeding thrombocytopenic patients with hematological malignancies. Issue 3 (23rd December 2021) - Ohanian, Maro; Cancelas, Jose A.; Davenport, Robertson; Pullarkat, Vinod; Hervig, Tor; Broome, Catherine; Marek, Kelly; Kelly, Mary; Gul, Zartash; Rugg, Neeta; Nestheide, Shawnagay; Kinne, Bridget; et al.
Abstract: Thrombosomes are trehalose‐stabilized, freeze‐dried group O platelets with a 3‐year shelf life. They can be stockpiled, rapidly reconstituted, and infused regardless of the recipient's blood type. Thrombosomes thus represent a potential alternative platelet transfusion strategy. The present study assessed the safety and potential early signals of efficacy of Thrombosomes in bleeding thrombocytopenic patients. We performed an open‐label, phase 1 study of single doses of allogeneic Thrombosomes at three dose levels in three cohorts, each consisting of eight patients who had hematologic malignancies, thrombocytopenia, and bleeding. Adverse events, dose‐limiting toxicities (DLTs), World Health Organization (WHO) bleeding scores, and hematology values were assessed. No DLTs were reported. The median age was 59 years (24–71). Most patients had AML (58%) or ALL (29%), followed by MDS (8%) and myeloproliferative neoplasm (4%). The WHO scores of 22 patients who were actively bleeding at a total of 27 sites at baseline either improved ( n = 17 [63%]) or stabilized ( n = 10 [37%]) through day 6. Twenty‐four hours after infusion, 12 patients (50%) had a clinically significant platelet count increase. Of eight patients who received no platelet transfusions for 6 days after Thrombosomes infusion, 5 had a clinically significant increase in platelet count of ≥5000 platelets/μL and 2 had platelet count normalization. Thrombosomes doses up to 3.78 × 10 8 particles/kg demonstrated safety in 24 bleeding, thrombocytopenic patients with hematological malignancies. Thrombosomes may represent an alternative to conventional platelets to treat bleeding. A phase 2 clinical trial in a similar patient population is underway.